(untitled) (Al-Academy, 2026)
This study examines the application of biogeometric art motifs in contemporary men’s fashion design within the framework of modern trends that integrate aesthetic, functional, and psychological dimensions of clothing. It is based on the assumption that organized geometric systems and harmonious relationships derived from nature can enhance design quality and promote a sense of comfort. This raises the question of the effectiveness of this approach in men’s fashion, where its application remains limited. To achieve this objective, the study adopts both descriptive-analytical and applied methodologies. A set of design proposals inspired by biogeometric motifs was developed and evaluated using a questionnaire administered to a sample of specialists and consumers. The evaluation focused on two main aspects: aesthetic and functional, supported by statistical analysis of the collected data. The results revealed statistically significant differences among the designs in both aspects, confirming the effectiveness of employing this approach in enhancing the aesthetic and functional values of the designs. Furthermore, the compositional relationships and harmony among decorative elements contributed to achieving clear visual balance, enhancing psychological comfort, and reducing visual tension. The study highlights the importance of adopting this approach in developing contemporary men’s fashion designs that consider psychological dimensions alongside aesthetic and functional aspects, thereby improving the overall quality of the design product.